2013
DOI: 10.1261/rna.037291.112
|View full text |Cite
|
Sign up to set email alerts
|

Secondary structure of bacteriophage T4 gene 60 mRNA: Implications for translational bypassing

Abstract: Translational bypassing is a unique phenomenon of bacteriophage T4 gene 60 mRNA wherein the bacterial ribosome produces a single polypeptide chain from a discontinuous open reading frame (ORF). Upon reaching the 50-nucleotide untranslated region, or coding gap, the ribosome either dissociates or bypasses the interruption to continue translating the remainder of the ORF, generating a subunit of a type II DNA topoisomerase. Mutational and computational analyses have suggested that a compact structure, including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 62 publications
2
21
0
Order By: Relevance
“…Our present experiments and recent in-vitro translation experiments performed in S30 extracts 10 showed that essentially no byp was observed with mRNAs that were truncated shortly after the coding gap. These findings appear to contradict previous results obtained using different reporters in vivo, which suggested that translational bypassing was observed even when the sequence beyond the fifth nucleotide after the landing codon was replaced by the reporter sequence 4 .…”
Section: Discussionsupporting
confidence: 57%
See 4 more Smart Citations
“…Our present experiments and recent in-vitro translation experiments performed in S30 extracts 10 showed that essentially no byp was observed with mRNAs that were truncated shortly after the coding gap. These findings appear to contradict previous results obtained using different reporters in vivo, which suggested that translational bypassing was observed even when the sequence beyond the fifth nucleotide after the landing codon was replaced by the reporter sequence 4 .…”
Section: Discussionsupporting
confidence: 57%
“…Previous work indicated that replacing the gene 60 sequence following the landing site by reporter constructs did not abolish bypassing 4,22 . On the other hand, the bypassing efficiency on truncated gene 60 mRNA in cell lysates was strongly diminished 10 . To assess the minimum length required for bypassing, we tested several mRNA constructs that were truncated at different positions downstream of the landing codon (Fig.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations